ANALISIS PENGARUH INFLASI TERHADAP PERTUMBUHAN EKONOMI DI KOTA PALANGKARAYA - Rossy Naptania; Nicolaus Fiermon H, Josia Ananta, Lidiae, Siana (Jurnal Ekonomi dan Bisnis, 2024)
The available space of a country to accommodate the supply of goods and services is referred to as economic growth, and is often measured using variables or indicators such as GDP and per capita income. prices tend to increase over time, and this increase in prices is generally known as inflation. A condition where prices continuously increase is also known as inflation. One of the main factors causing inflation is the increase in the amount of money in circulation, resulting in currency depreciation, especially if the central bank prints large amounts of money. This research explains the use of secondary data with the type of data applied, namely time series data from 1995 to 2022 obtained from BPS Palangka Raya City. This methodology uses research that includes quantitative and qualitative analysis which aims to assess the impact of inflation on economic growth. The calculation model applied contains simple linear regression research with the aim of analyzing the relationship between inflation and economic growth. By adopting literature methods to collect data. The method used for documentation is by searching for data related to a thing or variable in the form of notes or written information, etc. Inflation has a positive or negative relationship with the level of economic growth (Suhendra, 2016). The inflation situation in Palangka Raya City over the past 20 years tends to be classified as inflationary, with an increase of less than 10%. According to data from the Central Statistics Agency (BPS), the percentage rate of inflation in Central Kalimantan, where Palangka Raya City is located, is recorded at various levels from year to year. For example, in July, the inflation rate in Central Kalimantan reached 6.79 percent year-on-year. In January 2020, the inflation rate was 0.39 percent. Apart from that, BPS data shows that the inflation rate for Palangka Raya City in 2016 was around 1.91%. shows that there is a positive relationship between inflation and economic growth with a coefficient of 0.385. The direction of this positive relationship indicates that increasing inflation tends to cause an increase in the economic growth of Palangka Raya City during the 1995-2022 period. This research aims to examine the consequences of the influence on profit growth in the City of Palangka Raya from 1995 to 2022. From the results of the analysis, it can be concluded that inflation itself has a significant positive impact on the economic growth of the City of Palangka Raya during that period. This shows that when the inflation rate increases in a large city, profitable economic growth tends to increase naturally. This can be caused by several factors such as existing government programs and profitable sectors that are not too aflected by rising inflation.